Facile fabrication of an electrolyte-gated In2O3 nanoparticle-based thin-film transistor uniting laser ablation and inkjet printing. (22nd November 2018) - Hassan, Basem; Liang, You; Yong, Jason; Yu, Yang; Ganesan, Kumaravelu; Walla, Andrew; Evans, Robin; Chana, Gursharan; Nasr, Babak; Skafidas, Efstratios
Abstract: We propose the inkjet printing of new thin-film transistors (TFTs) based upon a sodium alginate (NaAlg) electrolyte–gate and a new In2 O3 nanoparticle ink in which the electrodes and channels were formed by laser ablation. Laser ablation improved the conductive ink channel resolution leading to a smaller channel length through low-temperature processing steps. The NaAlg based electrolyte and a thickness independent gate dielectric allow for an in-plane design resulting in relaxed manufacturing tolerance requirements and reduced processing steps/time. The fabricated TFT operates at a very low voltage (<1.5 V) with a measured field-effect mobility of 0.77 cm 2 V −1 s −1 and an ON/OFF current ratio exceeding 10 5 . The electrolyte-gated TFTs exhibit excellent durability over 1500 switching cycles and 10 days. The TFTs demonstrate no cytotoxicity in vitro, indicating that they have the potential to be suitable for low-cost environmentally friendly electronics and biosensor applications.